Development of E-Marketing Model Based on Android/iOS Application for Whale Shark Tourist Destination in Botubarani Village, Bonebolango Regency, Gorontalo - Mohamad, Rizki Aditya; Damayanti, Titien; Mertha, I Wayan (E-Journal of Tourism; Volume 11 Number 1 (March 2024)DO - 10.24922/eot.v11i1.112943, 2024)
This research is a research conducted to develop an android/iOS application-based e-marketing model in whale shark tourist destinations, Botubarani Village, Bonebolango Regency as one of the marketing media. This research was raised with the premise that information and communication technology is growing. Where information is available and can be accessed anytime and anywhere. The objective of this study is to create an e-marketing model for Whale Shark Tourist Destination in Botubarani Village, utilizing android/iOS platforms. This research uses qualitative methods with a descriptive approach with the main material in the form of primary and secondary data which aims to develop an e-marketing model based on android / iOS applications. Prototyping is an approach in software development that allows interaction between system developers and system users. The results of this study resulted in an android/iOS-based application developed as a marketing model for whale shark tourist destinations in Botubarani Village.